Business Design and Feasibility Of Doria Cafe Start Up Supported by Website Application in Bandung City - Litamurni, Fahira Alyayusi; Chumaidiyah, Endang (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2021)
Patria Donut is one of the start up businesses home-scale donut making established in 2018. Patria Donut produce in accordance with the number of orders from distributors and only in accordance with the desire to generate sales for end buyers. The location is difficult to reach by the customer makes this business unpopular. Seeing this fact, the owner wants to expand his business by opening a cafe in a more strategic location, in Jalan Lombok. We should do feasibility analysis by opening this cafÃ©. The market is conducted by spreading questionnaires to 100 respondents (target 16-39 years) in Bandung. The results showed a potential market of 86%, 98% available market, and the target market the company aimed at 0.8% of the available market. Meanwhile technical aspects and financial aspects based on secondary data from various sources. The financial calculation obtained from the NVP value for 2020-2024 are Rp 229.258.502,00, the IRR percentage is 26,69%, and PBP is 4 years and 4 months. IRR obtained is greater than the MARR value of 9.95% and NVP is positive. From these parameters, the opening of the Doria Cafe on Lombok Street, Bandung was feasible. We used website to support this business design.